Karakteristik Metodologi Pemahaman Hadis Era Modern: Tinjauan Komprehensif - Abror, Indal; Yahya, Nur Edi Prabha Susila (Journal of Hadith Studies, 2021)
The Hadith, as Islamic teachings, gave rise to a multitude of social interactions and understandings. The epistemology of the hadith has been established by hadith scholars, and the ulama of today are enhancing them with several kinds of innovative techniques that may be used to comprehend and apply them. However, in the contemporary era, these various methods continue to provide textual interpretation and a limited comprehension of hadith. This is analogous to realizing that women are not allowed to travel without a mahram. When the hadith is interpreted following the social context of the society, it will be fully understood and serve its intended purpose. To fully comprehend this article, we must have a contextual knowledge of hadith that incorporates several kinds of scientific disciplines. The context of Muhammad's prophetic message or other traditions should be taken into consideration while interpreting hadiths. The hadith will be able to bring out the principles of Islam itself, salihun likulli zaman wa makan, by thorough research and by referencing other scholarly works.